2008
DOI: 10.1159/000124341
|View full text |Cite
|
Sign up to set email alerts
|

Acquired Unilateral Melanocytic Nevi in Otherwise Normal Skin

Abstract: We describe a case with numerous melanocytic nevi in otherwise normal skin. A 5-year-old girl presented with more than 100 small pigment lesions on her left arm, shoulder and upper back without underlying light brown macule. The pigment lesions were first found on her left forearm at 3 months old and gradually increased along with her growth. Skin biopsy from a pigmented lesion shows a pathological change in compound-type melanocytic nevus without any atypical changes. Speckled lentiginous nevus is known to ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…MM have been reported to occur on all types of segmentally arranged melanocytic naevi, other than SN and SCMN. 5,6,12,18,19,[22][23][24] While this occurrence is not unexpected for mosaic DNS, there is not enough evidence to believe that the involved cutaneous segments carry a significantly increased risk of malignant degeneration.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…MM have been reported to occur on all types of segmentally arranged melanocytic naevi, other than SN and SCMN. 5,6,12,18,19,[22][23][24] While this occurrence is not unexpected for mosaic DNS, there is not enough evidence to believe that the involved cutaneous segments carry a significantly increased risk of malignant degeneration.…”
Section: Discussionmentioning
confidence: 99%
“…In two cases, MM occurred within the involved segment, while in another case, BN were also present . One patient also had an ipsilateral achromic naevus . Genetic testing was carried out on only one case, and showed a mosaic mutation of BRAF …”
Section: Blue Naevi Spitz Naevi and Common Acquired Melanocytic Naevimentioning
confidence: 97%
See 1 more Smart Citation
“…This hypothesis is not yet supported by a molecular study. Nonetheless, even though demonstrated in a keratinocytic model, a recent study identified a putative molecular basis of linear nonepidermolytic, nonorganoid keratinocytic epidermal nevi [8] . In this study, linear epidermal nevi could be linked to postzygotic mutations in the fibroblast growth factor receptor 3 gene (tyrosine kinase receptor), which occurred in a single keratinocyte stem cell at an early stage of the embryonic development [9] .…”
Section: Introductionmentioning
confidence: 99%
“…A recent case of acquired numerous melanocytic nevi arranged in a linear pattern on the left arm has been described and considered as an unusual type of mosaicism of melanocytic disorders [8] . The concept of mosaicism could give an attractive explanation of the linear distribution of the nevus as observed in our case and those of Happle and Effendy [6] .…”
Section: Introductionmentioning
confidence: 99%